Building in Arcadia : the case for well-designed rural development - Reed, Ruth (Architect) (Riba Publishing, 2019)
Building in Arcadia: The case for well-designed rural development is a reasoned, impassioned and ultimately practical book identifying key barriers to rural development, and how planning applicants (whether householders, developers and landowners), and most particularly their agents who make the applications - architects, landscape architects or planners - can address, and overcome, them. Focusing on the positive aesthetic role buildings can play in the landscape, and proposing sensitive development, Building in Arcadia also explores the essential economic, social and Environmental case for more building in the countryside to make the countryside more viable. In so doing, it will actively engage, challenge and provoke debate - as well as offering practical ways forward.